Revision of Palaearctic Idiotypa (Hymenoptera, Diapriidae, Diapriinae, Spilomicrini) - Chemyreva, Vasilisa G.; Notton, David G.; Zaldívar-Riverón, Alejandro (Zootaxa, 2021)
A revision of the Palaearctic species of the genus Idiotypa Förster is provided. The genus Eunuchopria Szabó, 1961 is a junior synonym of Idiotypa Förster, 1856 syn. n. and the new combination Idiotypa nitens (Szabó, 1961) comb. n., is established. Dublicate original spellings I. marii and I. mariae are resolved by first reviser action; I. mariae is now the correct original spelling. Lectotypes are designated for Idiotypa mariae and I. maritima. New synonymy is proposed: I. maritima (Haliday, 1833) = I. rufiventris (Thomson, 1858) syn. n.; = I. nigriceps Kieffer, 1909 syn. n.; = I. nigriceps Kieffer, 1911 syn. n. The three valid species I. mariae Gregor, 1939, I. maritima (Haliday, 1833) and I. nitens (Szabó, 1961) are redescribed, illustrated and keyed.